Validity and reliability of a questionnaire to assess the impact of physical training and martial arts on physical fitness and psychological well-being in overweight secondary school students - Gengatharan, Kumaran; Nadzalan, Ali Md; Rashidin, Nurul Sazila; Yen Lee, Ernie Leong; Krishnan Vasanthi, Rajkumar; Pavlovic, Ratko; Shuxrat Ugli, Gaziev Shukurjon (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Childhood obesity is a pressing global issue, particularly among secondary school students, highlighting the need for effective interventions to mitigate its health impacts. As the first step to evaluate the effects of physical training and martial arts on the physical fitness and psychological states of overweight secondary school students, this study aimed to assess the validity and reliability of a newly developed questionnaire used to measure these outcomes. The questionnaire, comprising 37 items across four dimensions, was subjected to a rigorous validation process involving expert panels and reliability analysis, demonstrating good content validity (CVI = 0.87) and internal consistency reliability (overall Cronbach’s Alpha = 0.810). The results suggest that the questionnaire is a reliable and valid instrument for assessing the intended constructs. These findings have significant implications for the educational and public health sectors, advocating for the integration of physical training and martial arts interventions to combat obesity prevalence and promote healthier lifestyles among adolescents. This study provides valuable insights into the effectiveness of these interventions and their potential to improve the physical and psychological well-being of overweight secondary school students. Future research could explore the longitudinal effects and compare different intervention modalities to further inform evidence-based practices in addressing childhood obesity.